A hierarchical method for the impact force reconstruction in composite structures. (12th July 2019) - De Simone, Mario Emanuele; Ciampa, Francesco; Meo, Michele
Abstract: Impact damage is a major concern for new generation aircraft composite components due to their low impact resistance capabilities. The development of an impact location and force reconstruction algorithm would provide rapid and efficient prediction of damage occurrence, thus making structures safer and creating maintenance inspection procedures more efficient, thus saving time and costs. However, state-of-the-art impact force reconstruction algorithms use reference data from numerical simulations and require a detailed knowledge of mechanical properties, which are difficult to obtain under real operational conditions. This paper presents a hierarchical impact force reconstruction algorithm that relies on experimental structural responses measured by a sparse array of surface bonded receiving ultrasonic transducers. This algorithm uses time reversal method to retrieve the location of an impact source and interpolation techniques based on hierarchical radial basis functions to calculate the transfer function at the impact point and reconstruct the impact force history. A number of impact testing were performed on a composite plate-like structure and a wing stringer-skin panel, and compared with impact force algorithms available in literature. Experimental results revealed that the proposed impact force reconstruction method was able to extrapolate the information associated with points far from the impact location and determine the impact force history with high level of accuracy in a real aircraft structure. Since the proposed algorithm requires the calibration of transfer functions from a very sparse training set of data and it does not need numerical models of the component under investigation, it demonstrates its potential as a useful monitoring tool for impact force reconstruction in composite components for full-scale aircraft structural applications leading to timely and cost-efficient inspections.